Nongovernment reforestation in the Philippines: Review, analysis, and ways forward - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2015)
The study reviewed and assessed nongovernment reforestation in the Philippines vis-a-vis government and total reforestation using primary and secondary data. The end purpose was to identify issues and problems related to nongovernment reforestation and recommend actions that can be undertaken to address them. The study found that government reforestation dominated total reforestation while nongovernment reforestation only has a relatively small contribution in recent years. During the first three years of implementation of the National Greening Program, in particular, nongovernment reforestation had been erratic, increasing in 2011 but decreasing in 2012 and 2013. The study asserted that private reforestation, or reforestation conducted by the private sector under no agreement with the government, has been the main driver of nongovernment reforestation at present. However, its full development as an industry has been hindered by various institutional, production, and marketing issues and problems. The study recommended ways to address these problems and issues and move nongovernment reforestation forward.
Keywords: 330; non-government reforestation; private reforestation; reforestation laws and policies; generic supply chain; National Greening Program